Domestic banks as lightning rods? Home bias and information during Eurozone crisis - Orkun Saka (Bank of Finland, 2019)
European banks have been criticized for holding excessive domestic government debt during economic downturns, which may have intensified the diabolic loop between sovereign and bank credit risks. By using a novel bank-level dataset covering the entire timeline of the Eurozone crisis, I first re-confirm that the crisis led to the reallocation of sovereign debt from foreign to domestic banks. This reallocation was only visible for banks as opposed to other domestic private agents and it cannot be explained by the banks' risk-shifting tendency. In contrast to the recent literature focusing only on sovereign debt, I show that banks' private sector exposures were (at least) equally affected by a rise in home bias. Finally, consistent with these patterns, I propose a new debt reallocation channel based on informational frictions and show that informationally closer foreign banks increase their relative exposures when sovereign risk rises. The effect of informational closeness is economically meaningful and robust to the use of different information measures and controls for alternative channels of sovereign debt reallocation.
URN:NBN:fi:bof-201902051061
Keywords: F21; F34; F36; G01; G11; G21; 330